If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y = 2y + 72 Reorder the terms: 10y = 72 + 2y Solving 10y = 72 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 10y + -2y = 72 + 2y + -2y Combine like terms: 10y + -2y = 8y 8y = 72 + 2y + -2y Combine like terms: 2y + -2y = 0 8y = 72 + 0 8y = 72 Divide each side by '8'. y = 9 Simplifying y = 9
| 9.11*9.11= | | 9.15*9.15= | | -31+3a=4(a-7) | | x+3(2x+5)=6 | | -8(1+3x)-6x=172 | | n-8=19-11 | | 9.21*9.21= | | n^2-12n+13=-7 | | 3(r-5)+2(r-4)=-2(r-1)+8(r+2) | | 8(7r+5)=320 | | 6x-5=109 | | 8(7r+5)=330 | | e^4x=e^2x+6 | | 2/3=2-2 | | 2a+14-13=-7 | | a^2+8a+6=-9 | | b-33=145 | | 4+2(2)+3x=11 | | 6(1-5v)=-234 | | 6-2n=-8+3(-4n-2) | | 1-3y/5-4=2y/3 | | 4(3x-5)-12(x-5)=70 | | 1+3x=4+4x | | (2x-7)y=15 | | x=x-u | | -10-9k=-91 | | -8x-3x-11=-8x+7 | | 3x-10(x+2)=sqrt(13)-7x | | -8x-3x-11=-8+7 | | 99=5n+9 | | 4(3x-5)+12(x-5)=70 | | 6-6(5+5m)=-24+8m |